2016
DOI: 10.1016/j.memsci.2016.05.033
|View full text |Cite
|
Sign up to set email alerts
|

Nanofiltration membranes with dually charged composite layer exhibiting super-high multivalent-salt rejection

Abstract: a b s t r a c tState-of-the-art nanofiltration (NF) membranes generally positively or negatively charged could not remove both multivalent cations and anions once and for all according to the Donnan Exclusion. Designing NF membranes with facile approach for effective removal of multivalent-salt without compromising the permeation is still a tough challenge. In this work, we demonstrate a sort of novel NF membrane consists of a positively charged interlayer sandwiched between substrate and negatively charged ou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
35
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 90 publications
(35 citation statements)
references
References 47 publications
(52 reference statements)
0
35
0
Order By: Relevance
“…As seen from the Fig. 2(d) , it is clearly to observe that the signals at 1.25, 2.80, 3.58 and 5.29 ppm were attributed to the protons of -C H 2 -, O-C H 3 , -NH-C H 2 -C H 2 -NH- and -C H =C H -, respectively 31 , which appeared stronger with more displacement of chlorine with mannich base of WCOME, but the signal at 4.5 ppm corresponds to the protons of C H -Cl presented weaker gradually, which indicated that the self-plasticization PVC was obtained.…”
Section: Resultsmentioning
confidence: 82%
“…As seen from the Fig. 2(d) , it is clearly to observe that the signals at 1.25, 2.80, 3.58 and 5.29 ppm were attributed to the protons of -C H 2 -, O-C H 3 , -NH-C H 2 -C H 2 -NH- and -C H =C H -, respectively 31 , which appeared stronger with more displacement of chlorine with mannich base of WCOME, but the signal at 4.5 ppm corresponds to the protons of C H -Cl presented weaker gradually, which indicated that the self-plasticization PVC was obtained.…”
Section: Resultsmentioning
confidence: 82%
“…30 In addition, the displacement of chlorine with amidation derivatives was usually to modify PVC surfaces for preparing functional ultraltration membranes with improved antifouling properties. [31][32][33] Covalent immobilization of trypsin and chymotrypsin onto aminated-PVC microspheres was also descried by Li et al 34 However, the displacement of chlorine with aminated derivatives via single reaction for plasticizing PVC materials has never reported.…”
mentioning
confidence: 96%
“…Charge properties of samples were detected using an electrokinetic analyser (SurPASS, Anton Paar, Austria) [24]. Fibres were immobilized in a module in advance to analyse the charge properties of membrane inner surface.…”
Section: Membrane Characterizationmentioning
confidence: 99%
“…Furthermore, the solutes employed in membrane separation performance evaluation would also affect the research results. Unlike the dense RO membranes, the separation performance, particularly the salts rejection, of the relatively loose NFMs is significantly influenced by its charge properties, which are commonly determined by the content of -NH and -COOH groups in the separating layer [22][23][24].…”
Section: Introductionmentioning
confidence: 99%